2016
DOI: 10.2465/jmps.150829
|View full text |Cite
|
Sign up to set email alerts
|

Peak and post–peak development of UHT metamorphism at Mather Peninsula, Rauer Islands: Zircon and monazite U–Th–Pb and REE chemistry constraints

Abstract: Zircon and monazite in ultrahigh temperature (UHT) metamorphic rocks from the Rauer Islands of Prydz Bay in East Antarctica were investigated in terms of U-Th-Pb and rare earth elements (REE) chemistry along with textural context. All five analyzed samples, three from the Mather Paragneiss UHT unit and two from the host orthogneiss unit yield 522-517 Ma concordant zircon ages, with older protolith/inherited zircon ages of 3268 and 2800-2400 Ma along with highly discordant Mesoproterozoic to Neoproterozoic ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 45 publications
(146 reference statements)
1
5
0
5
Order By: Relevance
“…In this study, we investigate a single sample of highly residual metapelitic granulite (RG07‐21) from Lunnyj Island in the Rauer Group of the Prydz Belt, East Antarctica (Figure ; Harley & Fitzsimons, ; Kelsey, Hand, Clark, & Wilson, ). Previous studies have shown that the region experienced granulite facies metamorphism on at least two occasions, first during the Rauer Tectonic Event ( c. 1,170–910 Ma) and later ( c. 570–510 Ma) during the Prydz Tectonic Event (Harley, ; Hokada, Harley, Dunkley, Kelly, & Yokoyama, ; Kelsey, Wade, et al, ; Kelsey et al, ). The sample contains abundant coarse‐grained garnet and orthopyroxene along with quartz, biotite and cordierite, minor plagioclase and accessory rutile, ilmenite, zircon, and monazite.…”
Section: Introductionmentioning
confidence: 97%
“…In this study, we investigate a single sample of highly residual metapelitic granulite (RG07‐21) from Lunnyj Island in the Rauer Group of the Prydz Belt, East Antarctica (Figure ; Harley & Fitzsimons, ; Kelsey, Hand, Clark, & Wilson, ). Previous studies have shown that the region experienced granulite facies metamorphism on at least two occasions, first during the Rauer Tectonic Event ( c. 1,170–910 Ma) and later ( c. 570–510 Ma) during the Prydz Tectonic Event (Harley, ; Hokada, Harley, Dunkley, Kelly, & Yokoyama, ; Kelsey, Wade, et al, ; Kelsey et al, ). The sample contains abundant coarse‐grained garnet and orthopyroxene along with quartz, biotite and cordierite, minor plagioclase and accessory rutile, ilmenite, zircon, and monazite.…”
Section: Introductionmentioning
confidence: 97%
“…In neither the Mather or Napier Complex do the rutile preserve the UHT peak temperature, let alone UHT conditions. Rutiles in the Mather Paragneiss, which preserves a~20-30 Myr UHT-ITD P-T history (Harley, 1998b;Hokada et al, 2016), record temperatures following the end of the UHT-ITD and subsequent decompression-cooling path (Fig. 4c).…”
Section: Constraining Temperature and Time In Uht Metamorphismmentioning
confidence: 99%
“…лет и более молодой 540−510 млн. лет [Kinny, 1998;Kelsey et al, 2007Kelsey et al, , 2003aHokada et al, 2016].…”
Section: геологическая характеристика островов рёуерunclassified
“…В провинции Рейнер интервал времени 550−500 млн. лет интерпретируется как одно из основных высокотемпературных тектонотермальных событий (Прюдское событие, [Harley, Kelly, 2007b;Liu et al, 2013]), воздействовавших на породы, расположенные на восточном побережье залива Прюдс [Hensen, Zhou, 1995, Carson et al, 1996Fitzsimons et al, 1997;Harley and Kelly, 2007b;Mikhalsky et al, 2013;Hokada et al, 2016], т.е. на территории, непосредственно граничащей с исследованным районом.…”
Section: обсуждение результатовunclassified
See 1 more Smart Citation